Casting off the old Kaross: the Little Namaqualand missions, 1805-1848 - Rawson, Kathryn (Department of Historical Studies, 2022)
This thesis is a history of the development of missionary activity in the Little Namaqualand region of southern Africa during the first half of the nineteenth century. Through a rich analysis of the archival documents of the various missionary societies who worked in the region, it attempts to fill in the wide gaps present in the historical narrative. Little Namaqualand, an area north of the Olifants River and south of the Orange River, during the nineteenth century was the epicentre of the north-western frontier zone of the Cape Colony. It had long been home to the Little Namaqua, a Khoikhoi group, who occupied the central and mountainous region of the Kamiesberg, the San, who moved between the Kamiesberg and Bushmanland to the east, and ‘baster' (mixed race) groups who migrated from the Cape in the eighteenth century. It has since been a relatively under-studied area despite it being the hub of missionary activity in the north-west in the nineteenth century. An environmentally harsh and politically turbulent region, home to a nomadic people, it presented a unique and trying set of circumstances for the incoming missionaries. The European missionaries of the London Missionary Society (LMS), Wesleyan Missionary Society (WMMS) and later the Rhenish Missionary Society (RMS) moved through the region in waves during the early decades of the nineteenth century. Their intended destination, however, was not Little Namaqualand, but Great Namaqualand across the Orange River. For the first fifteen years of the century the missionaries moved between Little and Great Namaqualand, unable to establish a permanent and successful settlement. They faced many difficulties – the colonial government's changing attitudes and legislation towards missionary activities in and outside of the colony's borders, the mounting financial strain of maintaining a mission station in such a barren, desolate and sweltering region and existing inter-group tensions between those amongst whom they ministered. From their first arrival in the region in 1805, the early German missionaries of the LMS relied on local and powerful mixed-race groups to facilitate their stay, both financially and logistically. These groups had long been desirous of a missionary in the region for both their spiritual and temporal benefits. On the north-western frontier, access to trading networks and firearms was pivotal to the survival of many groups who relied almost solely on hunting and ivory trading. Many missionaries, themselves struggling to survive under such trying environmental conditions, themselves resorted to hunting and trading to supplement their pitiful income. By 1811, after a devastating attack on their Great Namaqualand mission, the LMS retreated into Little Namaqualand where they paid more attention to establishing themselves on a more permanent basis. A fresh wave of young and enthusiastic German missionaries greatly aided this effort. The Wesleyans joined shortly after in 1816. Both missionary societies were still understaffed and, due to unique regional circumstances, relied heavily on Namaqua and baster translators and teachers. Many of these would become missionaries in their own right. The northerly stations of Little Namaqualand, Steinkopf and Pella, utilised these African evangelists to run the various outposts or satellite stations (necessitated by the people's nomadic habits). The same took place at the southern stations of Leliefontein and Komaggas. From Leliefontein, several Namaqua converts were sent out. Many of them ministered to Sotho-Tswana and Coranna groups in the east. These African evangelists, and the pivotal role they played in facilitating and sustaining the Little Namaqualand missions, form the core of this thesis. Their names have been excavated from the archival records and the often limited anecdotes of their lives have been brought to life. This thesis shows that the spread of Christianity in the region pre-dated the formal arrival of the European missionaries. After their arrival, it was through African mouths that the message of Christianity took on a new form and was more successfully prorogated through the region. The majority of those who heard the gospel message responded emotionally. Most negotiated with what they heard, rejecting some tenets of the message while accepting others. They thus embraced and created a wholly new rendition of Christianity, one which saw to their immediate needs and offered both a remedy and an explanation for their suffering.